Resolution therapy: Harnessing efferocytic macrophages to trigger the resolution of inflammation - Saas, Philippe; Vetter, Mathieu; Maraux, Melissa; Bonnefoy, Francis; Perruche, Sylvain (Frontiers in Immunology, 2022)
Several chronic inflammatory diseases are associated with non-resolving inflammation. Conventional anti-inflammatory drugs fail to completely cure these diseases. Resolution pharmacology is a new therapeutic approach based on the use of pro-resolving mediators that accelerate the resolution phase of inflammation by targeting the productive phase of inflammation. Indeed, pro-resolving mediators prevent leukocyte recruitment and induce apoptosis of accumulated leukocytes. This approach is now called resolution therapy with the introduction of complex biological drugs and cell-based therapies. The main objective of resolution therapy is to specifically reduce the duration of the resolution phase to accelerate the return to homeostasis. Under physiological conditions, macrophages play a critical role in the resolution of inflammation. Indeed, after the removal of apoptotic cells (a process called efferocytosis), macrophages display anti-inflammatory reprogramming and subsequently secrete multiple pro-resolving factors. These factors can be used as resolution therapy. Here, we review the different mechanisms leading to anti-inflammatory reprogramming of macrophages after efferocytosis and the pro-resolving factors released by these efferocytic macrophages. We classify these mechanisms in three different categories: macrophage reprogramming induced by apoptotic cell-derived factors, by molecules expressed by apoptotic cells (i.e., “eat-me” signals), and induced by the digestion of apoptotic cell-derived materials. We also evoke that macrophage reprogramming may result from cooperative mechanisms, for instance, implicating the apoptotic cell-induced microenvironment (including cellular metabolites, specific cytokines or immune cells). Then, we describe a new drug candidate belonging to this resolution therapy. This candidate, called SuperMApo, corresponds to the secretome of efferocytic macrophages. We discuss its production, the pro-resolving factors present in this drug, as well as the results obtained in experimental models of chronic (e.g., arthritis, colitis) and acute (e.g., peritonitis or xenogeneic graft-versus-host disease) inflammatory diseases.